Effect of specimen size and type on real-mode-I fracture toughness of hooked-end steel fiber-reinforced concrete (Fracture and Structural Integrity, 2026)
This paper studied the effects of specimen size and type on the real-mode-I fracture toughness (KIC )of steel fiber-reinforced concrete (SFRC) specimens. Mode I KIC tests were performed using semicircular bend (SCB) and center-cracked circular disk (CCCD) specimens with different sizes and crack-to-depth ratios, (a/R). SCB Specimens were tested under three-point bending, and CCCD specimens were tested under indirect tension test conditions to achieve pure Mode I crack growth. Moreover, KIC was analyzed as a function of specimen type (SCB and CCCD), specimen size (R values of 50, 75, 100, and 125 mm), and a/R ratios of 0.2, 0.3, 0.4, and 0.5. The results clearly show that the KIC of SFRC exhibits a distinct size effect: it increases with specimen radius up to a critical range of 75-100 mm, after which it levels off. The a/R ratio is an important parameter affecting the toughness; higher values of a/R result in increased KIC values, with increases of 12.9% for CCCD specimens and 22.7% for SCB specimens when a/R is raised from 0.2 to 0.5 at R=75 mm. In addition, the failure mode shifts from ductile fiber pull-out at shallow a/R to brittle fiber rupture at highera/R. The results also emphasize the importance of using geometry-adjusted models, such as Bazant's size effect law (SEL), especially when dealing with SFRC, since fiber distribution and crack-bridging efficiency depend on both size and geometry.
Keywords: Fracture toughness; Size effect; Semicircular bend (SCB); Center-cracked circular disk (CCCD); Matrix Crack; Fiber bridging mechanism